2016
DOI: 10.1038/srep19184
|View full text |Cite
|
Sign up to set email alerts
|

Livestock-associated methicillin and multidrug resistant S. aureus in humans is associated with occupational pig contact, not pet contact

Abstract: This study aimed to explore the association of livestock-associated S. aureus with occupational pig contact and pet contact. In this cross-sectional study, 1,422 participants (including 244 pig workers, 200 pet-owning workers and 978 control workers) responded to a questionnaire and provided a nasal swab for S. aureus analysis. Resulting isolates were tested for antibiotic susceptibility, the immune evasion cluster (IEC) genes, and multilocus sequence type. Compared with controls, the pig workers demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 41 publications
(69 reference statements)
3
27
1
Order By: Relevance
“…MRSA has been identified in retail foods worldwide. Human infections caused by MRSA take place via direct contact with farm animals or handling of food of animal products (Ye and others ). Pigs are currently regarded as the most important reservoir of livestock‐associated MRSA clones (Sun and others ; Ye and others ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MRSA has been identified in retail foods worldwide. Human infections caused by MRSA take place via direct contact with farm animals or handling of food of animal products (Ye and others ). Pigs are currently regarded as the most important reservoir of livestock‐associated MRSA clones (Sun and others ; Ye and others ).…”
Section: Discussionmentioning
confidence: 99%
“…Human infections caused by MRSA take place via direct contact with farm animals or handling of food of animal products (Ye and others ). Pigs are currently regarded as the most important reservoir of livestock‐associated MRSA clones (Sun and others ; Ye and others ). A large USA surveys (38 swine herds in 11 states) showed that 77% of pigs investigated were MRSA carriers (Sun and others ).…”
Section: Discussionmentioning
confidence: 99%
“…We examined prevalence of S. aureus , MRSA, and MDRSA nasal carriage outcomes, including several putative markers of LA- S. aureus — scn -negative S. aureus , S. aureus CC398, and S. aureus CC9 (Nadimpalli et al 2015; Rinsky et al 2013; Ye et al 2016a, 2016b)—among adults with occupational exposure to IHOs, adult community resident without occupational exposure to IHOs, and one child < 7 years of age living in the same household as each adult in rural southeastern North Carolina.…”
Section: Introductionmentioning
confidence: 99%
“…movement, coughing, and/or sneezing) [3]. Clonal complex (CC) 398 is the most widely described strain, although CC9 is increasingly reported in Asia [4,5] and the United States [6,7]. Nasal carriage and infection with LA- S .…”
Section: Introductionmentioning
confidence: 99%